A qualitative study on wildlife contact and healthcare-seeking behaviors among a cluster of Mani ethnic group in Manang district, Satun province of Thailand - Paisit Boonyakawee; Kanokwan Suwannarong; Thanomsin Ponlap; Kannika Thammasutti; Phitsanuruk Kanthawee; Nisachon Bubpa; Chularat Boonyakawee; Bagus Pradana; Songsak Sokamol (One Health, 2024)
Mani, or Maniq, or Sakai, are recognized as indigenous hunter-gatherers. Some are nomadic, while others have settled and modernized. Our knowledge of this ethnic group's healthcare-seeking and wildlife contact is limited. Thus, this qualitative study examined healthcare practices and wildlife interaction among a cluster of Mani ethnic group members in Manang District, Satun Province, Thailand, from November to December 2022.Four key informant interviews (KIIs) and focus group discussions (FGDs) were carried out, and the selection of the study respondents was based on information from a gatekeeper and local health officials. Coding, thematic, content, and triangulation analyses of audio transcriptions were implemented based on the study objectives.Mani's beliefs and lifestyle are deeply rooted in the forest, which significantly impacts numerous aspects of their lives. They encountered challenges such as food scarcity, legal issues, and access to modern healthcare. However, since obtaining national identification cards, their mobility has decreased. Their way of life has also changed, as they've become more dependent on outsiders. Nevertheless, they continue engaging in traditional practices such as gathering food, hunting in the forest, and treating illnesses with herbal remedies. They rarely develop serious illnesses. They have decided to seek treatment only if their condition persists or worsens. In addition, their knowledge of COVID-19, zoonotic diseases, and emerging animal-borne diseases was limited. In this regard, relevant governments and organizations should improve their health literacy about zoonotic diseases spread by wild animals to promote appropriate wildlife contact practices and reduce the potential risk of infection.